2011
DOI: 10.3389/fpls.2011.00084
|View full text |Cite
|
Sign up to set email alerts
|

Mining Functional Elements in Messenger RNAs: Overview, Challenges, and Perspectives

Abstract: Eukaryotic messenger RNA (mRNA) contains not only protein-coding regions but also a plethora of functional cis-elements that influence or coordinate a number of regulatory aspects of gene expression, such as mRNA stability, splicing forms, and translation rates. Understanding the rules that apply to each of these element types (e.g., whether the element is defined by primary or higher-order structure) allows for the discovery of novel mechanisms of gene expression as well as the design of transcripts with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 170 publications
0
8
0
Order By: Relevance
“…Our study suggested that a gene could be functionally important even at a small level of overexpression such as FOXM1 and MYBL2 if they act as upstream regulators of genes of interacting proteins involved in an important biological process (20). However, our study has following limitations: (a) All the findings are based upon computational analysis using integrated data of gene expression, PPI, TFs, and miRNAs; (b) Our study did not integrate the data of gene mutations and gene copy number variations, which could abolish the cis- and trans-regulatory elements of a gene resulting aberrant gene expression and cancer (9698); and (c) Finally, our study lacks the experimental validation and therefore need further experimental testing.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that a gene could be functionally important even at a small level of overexpression such as FOXM1 and MYBL2 if they act as upstream regulators of genes of interacting proteins involved in an important biological process (20). However, our study has following limitations: (a) All the findings are based upon computational analysis using integrated data of gene expression, PPI, TFs, and miRNAs; (b) Our study did not integrate the data of gene mutations and gene copy number variations, which could abolish the cis- and trans-regulatory elements of a gene resulting aberrant gene expression and cancer (9698); and (c) Finally, our study lacks the experimental validation and therefore need further experimental testing.…”
Section: Discussionmentioning
confidence: 99%
“…AREs are common cis-regulatory elements of 3′-untranslated regions (UTR) of eukaryotic messenger RNAs and are important determinants of mRNA stability in mammals. Proteins binding to these elements can either increase or decrease mRNA stability and thus affect protein expression levels ( Ahmed et al, 2011 ). The mRNA of the endothelin ET-1 contains in its 3′-UTR an ARE forming a secondary structure.…”
Section: Animal Gapdh: Redox-dependent Non-glycolytic (Moonlighting) mentioning
confidence: 99%
“…However, to improve sensitivity and specificity of cellular IRES elements in VIPS, new algorithms can be implemented to simulate real relationships and interactions between 40s rRNA and IRES elements in next version of our prediction system. The new bioinformatic tool plays a major role in creating databases and finding eukaryotic functional elements such as IRES, iron-responsive elements, splicing regulatory elements.. etc [28]. Therefore, VIPS will be a useful internet resource for IRES elements location before experimental studies.…”
Section: Discussionmentioning
confidence: 99%